FABRICATION OF NANO CLAY INTERCALATED POLYMERIC MICROBEADS FOR CONTROLLED RELEASE OF CURCUMIN - PALLERLA, DHARMENDER; BANOTH, SUMAN; JYOTHI, SUNKARI (International Journal of Applied Pharmaceutics, 2021)
Objective: The objective of this study was to formulate and evaluate the Curcumin (CUR) encapsulated sodium alginate (SA)/badam gum (BG)/kaolin (KA) microbeads for controlled drug release studies. Methods: The fabricated microbeads were characterized by fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), X-ray diffraction (X-RD), and scanning electron microscopy (SEM). Dynamic swelling studies and in vitro release kinetics were performed in simulated intestinal fluid (pH 7.4) and simulated gastric fluid (pH 1.2) at 37 °C. Results: FTIR confirms the formation of microbeads. DSC studies confirm the polymorphism of CUR in drug loaded microbeads which indicate the molecular level dispersion of the drug in the microbeads. SEM studies confirmed the microbeads are spherical in shape with wrinkled and rough surfaces. XRD studies reveal the molecular dispersion of CUR and the presence of KA in the developed microbeads. In vitro release studies and swelling studies depend on the pH of test media, which might be suitable for intestinal drug delivery. The % of drug release values fit into the Korsmeyer-Peppas equation and n values are obtained in the range of 0.577-0.664, which indicates that the developed microbeads follow the non-Fickian diffusion drug release mechanism. Conclusion: The results concluded that the CUR encapsulated microbeads are potentially good carriers for controlled drug release studies.